A note on estimating minimal changeover time. Issue 1 (1st January 2017) - Hermel, Dror; Medina, Oded; Shvalb, Nir
Abstract : We propose a novel approach for the estimation of change-over times in a continuous production environment, and discuss the importance and prospects of our suggested framework through an illustrative example.